South Africa’s foreign policy consistencies and contradictions since 1994: A case study of soft power–soft disempowerment - MacLeod, Cristan Lee (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.